Lipoprotein (a) levels are not associated with carotid plaques and carotid intima media thickness in statin-treated patients with familial hypercholesterolemia. Issue 1 (September 2015) - Bos, Sven; Duvekot, Martijne H.C.; Touw-Blommesteijn, Adriana C.; Verhoeven, Adrie J.M.; Mulder, Monique T.; Watts, Gerald F.; Sijbrands, Eric J.G.; Roeters van Lennep, Jeanine E.
Abstract Background Lipoprotein (a), also called Lp(a), is a cardiovascular disease (CVD) risk factor. Statins do not lower Lp(a), this may at least partly explain residual CVD risk in statin-treated patients with familial hypercholesterolemia (FH). We investigated the association of Lp(a) levels with atherosclerosis in these patients. Methods and results We performed ultrasonography in 191 statin-treated FH patients (50% men; 48 ± 15 years) to detect carotid plaques and determine carotid intima-media thickness (C-IMT). Patients with high versus low Lp(a) levels (≤0.3 g/L) had similar plaque prevalence (36 and 31%, p = 0.4) and C-IMT (0.59 ± 0.12 and 0.59 ± 0.13 mm, p = 0.8). Patients with and without plaques had similar Lp(a) levels (median 0.35 (IQR: 0.57) and 0.24 (0.64) g/L, respectively, p = 0.4). Conclusions The Lp(a) levels were not associated with atherosclerosis in the carotid arteries of statin-treated FH patients. This suggests that adequate statin treatment delays carotid atherosclerosis in FH independently of Lp(a) levels.